2019
DOI: 10.5935/abc.20190119
|View full text |Cite
|
Sign up to set email alerts
|

Global Longitudinal Strain Predicts Poor Functional Capacity in Patients with Systolic Heart Failure

Abstract: BackgroundLeft ventricular global longitudinal strain value (GLS) can predict functional capacity in patients with preserved left ventricular ejection fraction (LVEF) heart failure (HF) and to assess prognosis in reduced LVEF HF.ObjetiveCorrelate GLS with parameters of Cardiopulmonary Exercise Test (CPET) and to assess if they could predict systolic HF patients that are more appropriated to be referred to heart transplantation according to CPET criteria.MethodsSystolic HF patients with LVEF < 45%, NYHA functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Hence, determination of the relationship between GLS and exercise intolerance could potentially allow the prediction of CRF of patients with IHD based solely on ECG-derived GLS. The exercise intolerance prediction results from this study extend the findings of Maia et al [ 40 ] regarding GLS measured in patients with systolic heart failure. In this study, the GLS cut-off value for detecting a peak VO 2 of <14 mL/min/kg was −15.2.…”
Section: Discussionsupporting
confidence: 88%
“…Hence, determination of the relationship between GLS and exercise intolerance could potentially allow the prediction of CRF of patients with IHD based solely on ECG-derived GLS. The exercise intolerance prediction results from this study extend the findings of Maia et al [ 40 ] regarding GLS measured in patients with systolic heart failure. In this study, the GLS cut-off value for detecting a peak VO 2 of <14 mL/min/kg was −15.2.…”
Section: Discussionsupporting
confidence: 88%
“…And it could classify HF patients according to the functional capacity. 25 In this study, we found that GLS had a low predicted value of the disease severity, which may stratify the patients with unknown condition and therefore to deserve more differentiated treatment.…”
Section: Discussionmentioning
confidence: 63%
“…The mean value of the percentage of longitudinal deformation of each segment is what we call the global longitudinal strain (GLS) and this index has shown to be an excellent parameter for systolic function evaluation, which is sensitive enough to detect incipient impairment when the ejection fraction is still normal and has a higher prognostic value than EF in many clinical situations. [5][6][7] In this issue of the Brazilian Archives of Cardiology, Dr. Ronaldo Campos Rodrigues presents us with an excellent work, in which left ventricular systolic function was assessed by quantifying GLS in HIV-positive patients, with and without antiretroviral therapy, compared with a control group. 8 It was observed that GLS values were significantly lower in infected individuals than in control ones, regardless of whether or not they were undergoing treatment.…”
Section: Doi: 105935/abc20190198mentioning
confidence: 99%